White Matter Hyperintensities Relate to Basal Ganglia Functional Connectivity and Memory Performance in aMCI and SVMCI - Acharya, Alaka; Liang, Xia; Tian, Weiming; Jiang, Chuanlu; Han, Ying; Yi, Liye (Frontiers in Neuroscience, 2019)
Cerebral small vessel diseases play a crucial role in both vascular and non-vascular dementias. The location of white matter hyperintensities (WMHs), a neuroimaging marker of cerebral small vessel disease, has been found to vary between different types of dementias, with those in basal ganglia have been particularly associated with vascular cognitive impairment. However, anatomical variation of WMHs across basal ganglia nuclei and its effect on brain network dysconnectivity has not been clearly elucidated. The study sample consisted of 40 patients with amnestic mild cognitive impairment (aMCI), 40 with subcortical mild cognitive impairment (SVMCI), and 40 healthy control subjects. We examined the volume of WMH using T2-weighted magnetic resonance imaging. We also assessed the disturbances in BG-cortical communication by measuring resting-state functional connectivity (rsFC) from the functional magnetic resonance imaging signal. WMHs were more pronounced in SVMCI group particularly in the caudate regions. In SVMCI patients, while higher WMHs in dorsal caudate correlated with weaker FC with executive control regions and worse immediate recall performance, WMHs in ventral caudate were associated with weaker FC with anterior default mode regions and worse delayed recall performance. In contrast, in aMCI patients, basal ganglia WMHs were not correlated with their changes in functional connectivity changes, which showed weaker connectivity with almost all basal ganglia structures, rather than restricting to specific basal ganglia subdivisions as observed in SVMCI group. Our findings demonstrate that heterogeneously distributed basal ganglia WMHs are associated with changes in functional network interactions and verbal episodic memory performance only in SVMCI patient, which establishes a link between cerebrovascular-related structural abnormality, functional integrity of basal ganglia circuits, and episodic memory impairments in SVMCI, and may reflect a differential role of the cerebrovascular pathology in disrupting network-level communications and cognition between Alzheimer’s and subcortical vascular dementia.